Correlación entre composición lipídica y curvatura de membrana en la exocitosis : análisis biofísico-computacional - Suhaiman, L.; Borioni, J.L.; Ferguson, M.; Belmonte, S.; Del Popolo, M. G. (2019)
Fil: Suhaiman, L..